Can visual cortex non-invasive brain stimulation improve normal visual function? A systematic review and meta-analysis - Bello, Umar M.; Wang, Jingying; Park, Adela S. Y.; Tan, Ken W. S.; Cheung, Blossom W. S.; Thompson, Benjamin; Cheong, Allen M. Y. (Frontiers in Neuroscience, 2023)
Objective Multiple studies have explored the use of visual cortex non-invasive brain stimulation (NIBS) to enhance visual function. These studies vary in sample size, outcome measures, and methodology. We conducted a systematic review and meta-analyses to assess the effects of NIBS on visual functions in human participants with normal vision. Methods We followed the PRISMA guidelines, and a review protocol was registered with PROSPERO before study commencement (CRD42021255882). We searched Embase, Medline, PsychInfo, PubMed, OpenGrey and Web of Science using relevant keywords. The search covered the period from 1st January 2000 until 1st September 2021. Comprehensive meta-analysis (CMA) software was used for quantitative analysis. Results Fifty studies were included in the systematic review. Only five studies utilized transcranial magnetic stimulation (TMS) and no TMS studies met our pre-specified criteria for meta-analysis. Nineteen transcranial electrical stimulation studies (tES, 38%) met the criteria for meta-analysis and were the focus of our review. Meta-analysis indicated acute effects (Hedges’s g = 0.232, 95% CI: 0.023–0.442, p = 0.029) and aftereffects (0.590, 95% CI: 0.182–0.998, p = 0.005) of tES on contrast sensitivity. Visual evoked potential (VEP) amplitudes were significantly enhanced immediately after tES (0.383, 95% CI: 0.110–0.665, p = 0.006). Both tES (0.563, 95% CI: 0.230–0.896, p = 0.001) and anodal-transcranial direct current stimulation (a-tDCS) alone (0.655, 95% CI: 0.273–1.038, p = 0.001) reduced crowding in peripheral vision. The effects of tES on visual acuity, motion perception and reaction time were not statistically significant. Conclusion There are significant effects of visual cortex tES on contrast sensitivity, VEP amplitude, an index of cortical excitability, and crowding among normally sighted individuals. Additional studies are required to enable a comparable meta-analysis of TMS effects. Future studies with robust experimental designs are needed to extend these findings to populations with vision loss. Clinical trial registration ClinicalTrials.gov/, identifier CRD42021255882.